Biallelic mutations in PIGP cause developmental and epileptic encephalopathy. Issue 5 (11th April 2019) - Krenn, Martin; Knaus, Alexej; Westphal, Dominik S.; Wortmann, Saskia B.; Polster, Tilman; Woermann, Friedrich G.; Karenfort, Michael; Mayatepek, Ertan; Meitinger, Thomas; Wagner, Matias; Distelmaier, Felix
Abstract: Developmental and epileptic encephalopathies are characterized by infantile seizures and psychomotor delay. Glycosylphosphatidylinositol biosynthesis defects, resulting in impaired tethering of various proteins to the cell surface, represent the underlying pathology in some patients. One of the genes involved, PIGP, has recently been associated with infantile seizures and developmental delay in two siblings. Here, we report the second family with a markedly overlapping phenotype due to a homozygous frameshift mutation (c.456delA;p.Glu153Asnfs*34) in PIGP . Flow cytometry of patient granulocytes confirmed reduced expression of glycosylphosphatidylinositol‐anchored proteins as functional consequence. Our findings corroborate PIGP as a monogenic disease gene for developmental and epileptic encephalopathy.